Relación entre inversión pública y el desarrollo económico de la región Loreto periodo 2007 – 2024 - Vela Collazos, John Anderson (2025)
This research analyzes the relationship between public investment and economic development in the Loreto region during the 2007-2024 period. Using a quantitative approach with a non-experimental, correlational, and longitudinal design, key indicators such as per capita Gross Domestic Product (GDP), the Human Development Index (HDI), poverty rate, and formal and informal employment were evaluated. The results show a strong positive correlation between public investment and economic development, highlighting its impact on improving the population's well-being. A significant inverse relationship was found between per capita public investment and poverty rate, as well as between HDI and poverty, reaffirming the importance of public investment in reducing inequalities. However, formal employment rate showed a moderate correlation with budget execution, reflecting structural limitations in the labor market. Based on these findings, it is concluded that public investment is a fundamental driver of economic development, but its impact depends on its efficiency and sustainability. This study offers recommendations and strategic proposals to strengthen public investment in Loreto, promoting inclusive and sustainable development.